ENVIRONMENTAL RESPONSIBILITY AND FIRM FINANCIAL PERFORMANCE IN THE NORDIC COUNTRIES - Nurminen, Jaakko (My University, 2020)
Increasing attention of media and the public towards climate change issues and ongoing legislative procedures such as EU ETS and EU Action Plan are pressuring firms to act on behalf of a more sustainable future. As environmental issues affect us all, previous research suggests that the Nordic countries of Europe are seen to be more stakeholder-oriented and, thus, found to be the top performers among CSR. From the perspective of a firm, it is essential to match stakeholders’ increasing values towards environmental responsibility. Moreover, it is in the interest of investors, firms, and decision-makers to understand the potential underlying risk exposure environmental issues have on firm financial performance. This thesis contributes to the existing literature by first investigating the general relationship of environmental responsibility (ER) and firm financial performance (FP) in the Nordic countries during the sample period of 2002-2018. Secondly, as it is found by previous literature that strong ESG and ER contribution are negatively correlated with risk exposure of firms, this thesis investigates the strong and weak performance of ER and its potential effects on FP. For the purposes of this study, Finland, Sweden, Norway, and Denmark are considered as a proxy for the Nordics. Hence, the data of financial metrics and ER variables are derived from the all-share indices of Helsinki, Stockholm, Oslo, and Copenhagen over the sample period. The Environmental dimension of ESG, among the subdimensions of Emissions score, Environmental innovation, and CO2 and equivalent emissions operate as proxies for environmental responsibility in this study. Following previous research, ROA and Tobin’s q are considered as proxies for firm financial performance. All data has been derived from the Refinitiv (earlier Thomson Reuters) database. This study finds that ER measured with emissions control of firms is positively associated with FP measured with both ROA and Tobin’s q in the Nordics in general. Hence, this finding is confirmed with the negative relationship of CO2 and equivalent emissions and FP. Thus, markets seem to appreciate ER in the valuation of a firm. Regarding the weak performance of ER, the lack of emissions control shows some negative effects on ROA. Regarding the strong performance of ER, this study finds a positive association between ER and Tobin’s q. The findings of this study indicate that a strong contribution towards emissions control is beneficial for firms in terms of ROA and Tobin’s q. However, the findings regarding the weak and strong performance of ER and FP are not found to be that straightforward. Therefore, the generalization of the findings is needed to be taken with caution. Nevertheless, the findings of this study contribute to the existing literature by offering additional information regarding the risk exposure of firm and firm financial performance in the Nordics offering potential field for future studies of ER and FP.
Keywords: business; environmental responsibility; finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance